Prenatal ultrasound detection of fetal amniotic band ingestion in monochorionic diamniotic twin pregnancy: a rare case report - Somaye Shirazi Nejad; Maryam Roshan; Mohammad Saleh Jafarpishe; Peyman Hashemi; Mahdi Shahsavan; Mohammad Shahsavan (BMC, 2024)
Abstract Background Amniotic Band Syndrome (ABS) is a rare congenital condition characterized by the formation of fibrous bands within the amniotic sac that can entangle and restrict fetal development, leading to various deformities. In this report, we present an unprecedented case of fetal amniotic band ingestion in a monochorionic diamniotic (MCDA) twin pregnancy. Reporting this case is essential for expanding the understanding of the diverse presentations of amniotic bands, considering this rare entity in the differential diagnosis of prenatal ultrasound findings, and emphasizing the importance of vigilant prenatal monitoring and individualized management strategies. Case Presentation A 35-year-old gravida 2, para 1 woman with an MCDA twin pregnancy experienced an uneventful pregnancy until the 33rd week, when routine ultrasonography revealed mild intrauterine growth restriction in both twins. At 35 weeks and 5 days gestation, the patient presented with mild abdominal pain. An emergency ultrasound revealed that Twin A ingested an amniotic band. Despite the absence of overt fetal distress, a comprehensive risk assessment was conducted, taking into account potential complications, such as airway obstruction and gastrointestinal issues due to prolonged amniotic band ingestion. Considering the risks versus the benefits of continued gestation and the near-term status, an emergency cesarean section was performed. The procedure resulted in the successful delivery of both twins with satisfactory Apgar scores. A 9-cm fibrous strand was promptly extracted from Twin A's oral cavity after delivery, confirming prenatal diagnosis. Both neonates underwent thorough examinations, revealing no additional anomalies, and demonstrated normal development during the nine-month follow-up. Conclusion This case highlights the inherent challenges in diagnosing and managing the rare presentations of amniotic band-related complications, particularly in MCDA twin pregnancies. The instance of fetal amniotic band ingestion underscores the vital role of comprehensive prenatal imaging in ensuring accurate diagnosis and tailoring individualized risk assessments throughout the pregnancy in such rare and complex situations.